The star-crossed sisters of Tuscany [large type] - Spielman, Lori Nelson (Thorndike Press large print women's fiction series., 2020)
"When the fiercely independent and mysterious Paulina "Poppy" Fontana invites her great-nieces and fellow second-born daughters, Emilia and Lucy, to visit her birthplace of Italy, she makes a wild declaration. On her eightieth birthday, Poppy claims she'll meet the love of her life on the steps of the Ravello Cathedral and put an end to the Fontana Family Second-Daughter Curse once and for all. The Fontana Second-Daughter Curse is probably nothing but a coincidence, a self-fulfilling prophecy, an old-world myth. Even so, nobody can deny that for centuries, not a single second-born daughter in the Fontana family has married. But twenty-nine year-old Emilia actually appreciates the curse--some may even say she hides behind it. What might happen if the supposed curse is actually broken, and she's expected to find love? Reluctantly, the trio of second-born daughters embark on a journey to fulfill Poppy's last wish. Against a backdrop of lush Italian countryside and rich landmarks, Poppy shares family secrets and tales of forbidden love that threaten to upend every belief her young nieces have held to be true"--